The passing of the Hapsburg monarchy, 1914-1918. - MAY, ARTHUR J. (UNIV OF PENNSYLVANIA PRE, 1966)
The instructive story of the decline and collapse of this great power will have relevance not only for students of modern history but also for specialists in political science and for general readers who wish to understand the shape of central Europe.